The quantum age of IT : why everything you know about IT is about to change - Araujo, Charles (IT Governance Pub., 2012)
In The Quantum Age of IT, Charles Araujo examines what has led us to this point and what it means to the future of IT organizations. With a broad perspective on the fundamental changes affecting the industry, he offers practical guidance that every IT professional needs to compete in this new era of IT.